Information related to tobacco products in Indian undergraduate college syllabus: a content analysis - S., Anu Krishna Kumar; P. D., Madan Kumar (International Journal Of Community Medicine And Public Health, 2023)
Background: Health education through college textbooks is effective in promoting knowledge, reforming, and improving health related behaviours among youths. This study evaluated the amount of tobacco related health and other information among the undergraduate college syllabus in their curriculum. Methods: Under graduate college courses that were enrolled by students in the academic year 2019-2020 according to the All-India survey on higher education were included in the study. A total of 28 undergraduate courses under 12 governing bodies were included for content analysis. These curriculums were analysed by three examiners for the search of tobacco related keywords obtained from the WHO glossary of tobacco terms. The inter examiner reliability was calculated using the Cohen's Kappa in the SPSS software (version 25). Results: Total of 3383 pages of the curriculum from different undergraduate courses were analysed. Results showed that the total number of information related to tobacco appeared in the form of text as 15 and tabulations as 4, to a total of 19. Among the different courses, the tobacco-related contents were higher in MBBS curriculum. Distribution of the tobacco related contents under health information were found to be higher when compared to the tobacco cessation contents and laws. Conclusions: The distribution of tobacco related contents were found to be very less among the undergraduate courses. There is a lack of information regarding the cessation process and guidance against tobacco related habits.